CHARACTER EDUCATION MANAGEMENT PLANNING IN EARLY CHILDHOOD EDUCATION - Rezki Akbar Norrahman (Indonesian Journal of Education (INJOE), 2023)
This study aims to investigate character education management planning in the context of early childhood education. The main focus of this research is to design and implement an effective planning framework for character building at the early developmental stage of children. The methods used in this research included literature analysis, case studies, observations and interviews with educators. The results illustrate that character education management planning in early childhood education needs to consider children's developmental characteristics as well as the need for positive values formation. The planning model involves identifying relevant character values, developing interesting and developmentally appropriate lesson plans and implementing them through play and social interaction activities. The discussion highlights the importance of educators integrating character education in every aspect of early childhood learning. Planning that is tailored to children's characteristics helps shape positive attitudes, behaviors and interactions in the educational environment. The implications of this research support early character education efforts as an important foundation for children's personal development with integrity